One corner of the square : essays on the philosophy of Roger T. Ames - Sullivan, Ian M.; Mason, Joshua, 1978- (University of Hawaiʻi Press, 2021)
"In a historical moment when cross-cultural communication proves both necessary and difficult, the work of comparative philosophy is timely. Philosophical resources for building a shared future marked by vitality and collaborative meaning-making are in high demand. Taking note of the present global philosophical situation, this collection of essays critically engages the scholarship of Roger T. Ames, who for decades has had a central role in the evolution of comparative and nonwestern philosophy. With a reflective methodology that has produced creative translations of key Chinese philosophical texts, Ames-in conjunction with notable collaborators such as D.C. Lau, David Hall, and Henry Rosemont Jr.-has brought China's philosophical traditions into constructive cross-cultural dialogue on numerous ethical and social issues that we face today. The volume opens with two parts that share overlapping concerns about interpretation and translation of nonwestern texts and traditions. Parts III and IV-"Process Cosmology" and "Epistemological Considerations"-mark the shift in comparative projects from the metaphilosophical and translational stage to the more traditionally philosophical stage. Parts V and VI-"Confucian Role Ethics" and "Classical Daoism"-might best be read as Chinese contributions to philosophical inquiry into living well or "ethics" broadly construed. Lastly, Part VII takes Amesian comparative philosophy in "Critical Social and Political Directions," explicitly drawing out the broader dimensions of social constitution and the ideal of harmony. The contributors-scholars working in philosophy, religious studies, and Asian studies-pursue lines of inquiry opened up by the work of Roger Ames, and their chapters both clarify his ideas and push them in new directions. They survey the field of Chinese philosophy as it is taking shape in the wake of Ames's contributions and as it carries forward a global conversation on the future of humanity"-- Provided by publisher.
Keywords: Ames, Roger T., -- 1947-; Philosophy, Chinese.; Philosophy, Comparative.; Philosophie chinoise.; Philosophie comparée.; RELIGION / Confucianism.; Philosophy, Chinese; Philosophy, Comparative; China history.; Confucianism.; eastern philosophy.; methodology.; Essay; essays.; Essays; Essays.; Essais.